Functional Group Profiling of Gelatin-Based Transparent Capsule Shells Using FTIR-ATR Spectroscopy - Saddam Husein; Rafi Andrean Permana; Putri Amalia; Candra Saka Nusantari (Universitas Nusa Bangsa, 2026)
Transparent capsule shells are widely used as oral dosage forms; however, information regarding the source of gelatin is often unclear, potentially affecting product quality, safety, and halal status. This study aimed to profile ten samples of transparent capsule shells obtained from online stores using Fourier Transform Infrared Spectroscopy-Attenuated Total Reflectance (FTIR-ATR) and to compare their spectral characteristics with bovine, porcine, and fish gelatin standards. This laboratory experimental study employed FTIR-ATR analysis within the wavelength range of 4500-650 cm⁻¹. The results demonstrated that all capsule samples exhibited characteristic gelatin absorption bands in the Amide A, Amide I, Amide II, and Amide III regions. Based on Principal Component Analysis (PCA) and comparison with gelatin standards, 9 out of 10 samples (90%) showed spectral similarity to porcine gelatin, while 1 sample (10%) showed similarity to fish gelatin. No samples demonstrated dominant similarity to bovine gelatin. Sample K2 was classified as being closer to fish gelatin, whereas samples K1, K3, K4, K5, K6, K7, K8, K9, and K10 were classified as being closer to porcine gelatin. These findings indicate that FTIR-ATR is effective for profiling the chemical characteristics of transparent capsule shells and can be utilized as an analytical tool for identifying gelatin sources, thereby supporting quality control and consumer safety